Street with no name : a history of the classic American film noir - Dickos, Andrew, 1952- (Book collections on Project MUSE., 2002)
A Choice Outstanding Academic Title Flourishing in the United States during the 1940s and 50s, the bleak, violent genre of filmmaking known as film noir reflected the attitudes of writers and auteur directors influenced by the events of the turbulent mid-twentieth century. Films such as Force of Evil, Night and the City, Double Indemnity, Laura, The Big Heat, The Killers, Kiss Me Deadly and, more recently, Chinatown and The Grifters are indelibly American. Yet the sources of this genre were found in Germany and France and imported to Hollywood by emigré filmmakers, who developed them and.